Efficient decomposition of perfluorooctane sulfonate by electrochemical activation of peroxymonosulfate in aqueous solution: Efficacy, reaction mechanism, active sites, and application potential. (1st August 2022) - Li, Meng; Jin, Yu-Ting; Cao, Dan-Yang; Yang, Ling-Ling; Yan, Jian-Fang; Zhang, Zhao-Xin; Liu, Zhang; Huang, Long-Wei; Zhou, Shao-Qi; Cheng, Ji-Liang; Zhao, Qinglan; Zhao, Hai-Ming; et al.
Highlights: The diatomite and cerium co-modified Sb2 O3 anode shows excellent performance. Electron transfer and hydroxyl radical are responsible for the removal of PFOS. Electrochemical process exhibits strong tolerance to various ions in degrading PFOS. The electron transfer can damage the stable structure of PFOS. The potential energy difference can drive the electron transfer from HOMO to LUMO. Abstract: The electrochemical oxidation method is a promising technology for the degradation of perfluorooctane sulfonate (PFOS). However, the elimination processes of PFOS are still unknown, including the electron transfer pathway, key reactive sites, and degradation mechanism. Here, we fabricated diatomite and cerium (Ce) co-modified Sb2 O3 (D-Ce/Sb2 O3 ) anode to realize efficient degradation of PFOS via peroxymonosulfate (PMS) activation. The transferred electron and the generated hydroxyl radical (OH) can high-effectively decompose PFOS. The electron can be rapidly transferred from the highest occupied molecular orbital of the PFOS to the lowest unoccupied molecular orbital of the PMS via the D-Ce/Sb2 O3 driven by a potential energy difference under electrochemical process. The active site of Ce-O in the D-Ce/Sb2 O3 can greatly reduce the migration distance of the electron and the OH, and thus improving the catalytic activity for degrading various organic micropollutants with high stability. In addition, the electrochemical process shows strong resistance and tolerance to the changing pH, inorganic ions, and organic matter. This study offers insights into the electron transfer pathway and PMS activation mechanism in PFOS removal via electrochemical oxidation, paving the way for its potential application in water purification. Graphical abstract: Image, graphical abstract .